PERBEDAAN SIKAP WANITA USIA SUBUR TERHADAP PEMERIKSAAN IVA SEBELUM DAN SESUDAH DIBERIKAN PENYULUHAN TENTANG KANKER SERVIKS DI WILAYAH KERJA PUSKESMAS KEPANJEN: DIFFERENCES IN THE ATTITUDES OF FERTILE AGE WOMEN TOWARDS IVA EXAMINATION BEFORE AND AFTER COUNSELING ABOUT CERVICAL CANCER IN THE WORK AREA OF THE KEPANJEN PUBLIC HEALTH CENTER - Angesti, Herlina Puji; Wulandari, Endah Sri; Murtofiah, Siti (LPPM STIKes Bahrul Ulum Jombang, 2024)
Background: Cervical cancer is a public health problem both in the world and in Indonesia. Cervical cancer is the third leading cause of cancer death in women after breast cancer and lung cancer. Cervical cancer is cancer of the cervix, which is the area of the female reproductive organs which is the entrance to the uterus, which is located between the uterus and the vagina. Cervical cancer is attacks women of productive age aged 35-50 years. This study aims to determine the differences in the attitudes of women of childbearing age before and after being given counseling about cervical cancer. Subjects and Methods: The study used the pre-experimental one group pretest-posttest design method. The study was conducted on April 1-30, 2024 with a research sample of 100 people using the purposive sampling technique. Data analysis using the Sign Test processed with SPSS software version 26. Results: The test results show a p-value of 0.000 where the p-value ≤ 0.05, so it can be stated that H0 is rejected and H1 is accepted Conclusion: There are differences in the attitudes of women of childbearing age towards IVA examinations before and after being given counseling about cervical cancer. Based on the results of this study, it is recommended that women of childbearing age can pay attention to reproductive health by conducting IVA examinations as a prevention of cervical cancer